Analisis Patah Lelah Pipa Cold Superheater Boiler PLTU 2 Banten – Labuan - Andika Widya Pramono; Ari Yulianto (JURNAL POWERPLANT, 2013)
Boilers (Boiler) is a major component in the plant in which there are pipes steam boiler that serves to drain the water to be heated by the flame or hot gases to be steam. Boiler pipes are arranged into a single entity, starting from the steam drum, the combustion chamber (furnace / burner), superheater and economizer. The existing pipe in the boiler is a vital component, because the pipe is used as a container to drain the vapor or liquid throughout the existing system with high operating temperatures. It depends on the type of material engineering digunakan.Pipa boiler operating at high temperature and pressure in the long term is a problem that often occurs is in the form of leaks that resulted in the power plant should cease to operate as it did on 2 Banten Labuan power plant. Boiler pipe leakage at this plant occurs in areas of cold pipe boiler superheater in the form of fracture mechanics and surface defects due to the weld metal splashes. To overcome this, a boiler pipe to be analyzed by observing the microstructure, chemical composition analysis and micro hardness tester with Vickers method to determine the cause of the leak. In the sample cold pipe fracture failure occurs supeheater tired (fatigue failure) that is indicated on the beach mark (the beach) and striation. From the results shows that the chemical composition of the material cold pipe superheater in accordance with the standard specifications (ASTM A210 Grade C), so that failure and damage of all pipes that are not investigated due to the specifications of the material are not standardized.